MoS2–ZnO nanocomposites as highly functional agents for anti-angiogenic and anti-cancer theranostics. Issue 19 (25th April 2018) - Chacko, Levna; Poyyakkara, Aswini; Kumar, V. B. Sameer; Aneesh, P. M.
Abstract : Unlike the parent compounds, MoS2 –ZnO nanocomposites exhibit anti-tumor and anti-angiogenesis properties. Abstract : Due to its excellent properties, 2D-MoS2 finds potential applications in the fields of electronics, optoelectronics, energy storage and conversion, biomedicine, etc. This work deals with the incorporation of ZnO into 2D-MoS2, its structural, morphological, optical, and magnetic studies and its application as an efficient cancer therapeutic agent. The MoS2 –ZnO nanocomposite exhibits remarkable excitation wavelength dependent down-conversion and up-conversion photoluminescence. The observation of wasp-waisted magnetism in the MoS2 –ZnO nanocomposite indicates the coupling of ZnO and MoS2 materials inducing multimodal population. The MoS2 –ZnO nanocomposite showed cytotoxic properties with a safety index reaching up to ∼2. An in ovo xenograft assay revealed that the MoS2 –ZnO nanocomposite retards tumor growth by specifically activating caspase-3 and thereby inducing cellular apoptosis. Moreover, the treatment of xenografts with the MoS2 –ZnO nanocomposite down regulated the expression of major pro-angiogenic genes such as VEGF, VEGFR2 etc. thereby curtailing vascularization into the tumor intima. Treatment of tumor xenografts with the MoS2 –ZnO nanocomposite caused reduced expression of mesenchymal specific genes and elevated expression of epithelial specific genes, implying a role of the MoS2 –ZnO nanocomposite in retarding the process of epithelial to mesenchymal transition (EMT). This study highlights that the introduction of ZnO into MoS2 nanostructures offers a unique idea to design efficient MoS2 -based multifunctional nanocomposites that provide opportunities in advanced biomedical and optoelectronic applications.